POFMA: why and how - Zhang, Xue (2022)
POFMA (Protection from Online Falsehoods and Manipulation Act) has come into force for almost three years since 2 Oct 2019. Why do we need POFMA? What and how actions have been taken under POFMA? And what can we do as netizens? This commentary discusses these issues.